Analisis Program Bantuan Sosial (Survey Pemetaan Tingkat Kepuasan Bantuan Sosial Pada Dinas Sosial Kota Surakarta) - Yuli Hartono (Jurnal Ekonomi Manajemen Perbankan, 2020)
The purpose of this research is to find out the satisfaction of the people of Surakarta in the service program of the Family Hope Program (PKH), Non-Cash Food Assistance (BPNT), Poor Families (GAKIN) and Pilgrimage in the Surakarta Social Service and as material in setting service policies the public in carrying out continuous improvement in order to improve the quality of the next service quality.The method used in this research is descriptive analysis and verification analysis. Understanding the analysis of descriptive analysis according to Sugiyono (2005: 1) is: Research conducted to determine the value of the independent variable, either one variable or more (independent) without making comparisons or connecting between variables one with other variables. The data collection technique is using observation, interviews, and documentation and literature studies.Based on the results of research through observation, interviews and questionnaires concluded that the Family Hope Program (PKH) service program, Non-Cash Food Assistance (BPNT) is Very Good, the GAKIN service program is Good and the Pilgrimage Program is Poor.